Biochemical Principles and Functional Aspects of Pipecolic Acid Biosynthesis in Plant Immunity. Issue 1 (22nd March 2017) - Hartmann, Michael; Kim, Denis; Bernsdorff, Friederike; Ajami-Rashidi, Ziba; Scholten, Nicola; Schreiber, Stefan; Zeier, Tatyana; Schuck, Stefan; Reichel-Deland, Vanessa; Zeier, Jürgen
Abstract : The immune regulator pipecolic acid is synthesized by ALD1-mediated conversion of l -Lys to 2, 3-dehydropipecolic acid and consecutive reduction, to which Arabidopsis SARD4/ORNCD1 largely contributes. Abstract: The nonprotein amino acid pipecolic acid (Pip ) regulates plant systemic acquired resistance and basal immunity to bacterial pathogen infection. In Arabidopsis ( Arabidopsis thaliana ), the lysine (Lys) aminotransferase AGD2-LIKE DEFENSE RESPONSE PROTEIN1 (ALD1) mediates the pathogen-induced accumulation of Pip in inoculated and distal leaf tissue. Here, we show that ALD1 transfers the α-amino group of l -Lys to acceptor oxoacids. Combined mass spectrometric and infrared spectroscopic analyses of in vitro assays and plant extracts indicate that the final product of the ALD1-catalyzed reaction is enaminic 2, 3-dehydropipecolic acid (DP ), whose formation involves consecutive transamination, cyclization, and isomerization steps. Besides l -Lys, recombinant ALD1 transaminates l -methionine, l -leucine, diaminopimelate, and several other amino acids to generate oxoacids or derived products in vitro. However, detailed in planta analyses suggest that the biosynthesis of 2, 3-DP from l -Lys is the major in vivo function of ALD1. Since ald1 mutant plants are able to convert exogenous 2, 3-DP into Pip, their Pip deficiency relies on the inability to form the 2, 3-DP intermediate. The Arabidopsis reductase ornithine cyclodeaminase/μ-crystallin, alias SYSTEMIC ACQUIRED RESISTANCE-DEFICIENT4 (SARD4), converts ALD1-generated 2, 3-DP into Pip in vitro. SARD4 significantly contributes to the production of Pip in pathogen-inoculated leaves but is not the exclusive reducing enzyme involved in Pip biosynthesis. Functional SARD4 is required for proper basal immunity to the bacterial pathogen Pseudomonas syringae . Although SARD4 knockout plants show greatly reduced accumulation of Pip in leaves distal to P. syringae inoculation, they display a considerable systemic acquired resistance response. This suggests a triggering function of locally accumulating Pip for systemic resistance induction.